Sagittal plane fore hoof unevenness is associated with fore and hindlimb asymmetrical force vectors in the sagittal and frontal planes. - Sarah Jane Hobbs; Sandra Nauwelaerts; Jonathan Sinclair; Hilary M Clayton; Willem Back (PLoS ONE, 2018)
Asymmetry in forelimb dorsal hoof wall angles, termed unevenness, is associated with forelimb gait asymmetries, but compensatory mechanisms and out of plane ground reaction forces (GRFs) due to unevenness have yet to be documented. The aim of this study was therefore to investigate the effects of fore hoof unevenness on contralateral fore and hind limb force vectors patterns, in both sagittal and frontal planes. A group of n = 34 riding horses were classified into four groups: hoof angle difference of more than 1.5 degrees (UNEVEN; n = 27), including higher left fore (HIGH-LF; n = 12), higher right fore (HIGH-RF; n = 15), and hoof angle difference of less than 1.5 degrees (EVEN; n = 7). Three dimensional ground reaction forces GRFs were collected during trotting. GRF summary vectors representing the magnitude (VecMag) and angular direction (VecAng) of the entire stance phase in the sagittal and the frontal plane were calculated. The effects of unevenness on GRF production were explored using linear regression, repeated measures ANOVA and statistical parametric mapping (SPM) with significance at (P<0.05). In all uneven groups, increasing unevenness affected sagittal VecAng values in the forelimbs, with more propulsive GRF in the high hoof. In the HIGH-RF group, medial GRFs were also found in the high RF hoof compared to lateral GRFs in the low LF hoof (RF VecAng: 0.97±1.64 (deg); LF VecAng: -0.64±1.19 (deg); P<0.05). In both HIGH groups, compensatory associations to increasing unevenness were only found in the RH, but also a significantly greater lateral VecAng was found in the LH (P<0.05) compared to the RH limb. No significant differences (P>0.05) were found between hindlimb pairs in the EVEN group. Unbalanced sagittal and increased frontal plane GRFs in uneven horses suggest that they have greater locomotory challenges, as the equine musculoskeletal system is not constructed to withstand movement and loading in the frontal plane as effectively as it is in the sagittal plane.